Intelligence, education level, and risk of Parkinson’s disease in European populations: A Mendelian randomization study - Shi, Jingjing; Tian, Jie; Fan, Yu; Hao, Xiaoyan; Li, Mengjie; Li, Jiadi; Ma, Dongrui; Guo, Mengnan; Li, Shuangjie; Xu, Yuming; Shi, Changhe (Frontiers in Genetics, 2022)
Abstract Background: A high level of education or intelligence (IQ) is reported to be a risk factor for Parkinson’s disease (PD). The purpose of this study was to systematically examine the causal relationships between IQ, educational attainment (EA), cognitive performance, and PD. Methods: We used summary statistics from genome-wide association studies on IQ, EA, cognitive performance, and PD. Four genome-wide association study (GWAS) data for PD were used to comprehensively explore the causal relationship, including PD GWAS (regardless of sex), age at onset of PD GWAS, male with PD GWAS, and female with PD GWAS data. We conducted a two sample mendelian randomization (MR) study using the inverse-variance weighted (IVW), weighted median, simple mode, and weighted mode methods to evaluate the causal association between these factors. MR-Egger and MR-PRESSO were used for sensitivity analysis to test and correct horizontal pleiotropy. Multivariate MR(MVMR) was also used to account for the covariation between IQ, EA, and cognition, as well as to explore potential mediating factors. Results: Genetically predicted higher IQ was associated with an increased risk of PD in the entire population, regardless of gender. In the analyses using the IVW method, the odds ratio was 1.37 (P = 0.0064). Men with a higher IQ, more years of education, or stronger cognitive ability are more likely to develop PD compared to women. MVMR showed that adjusting for education and cognition largely attenuated the association between IQ and PD, suggesting that education and cognition may mediate the effect of IQ on PD. Conclusion: This study provides genetic support for the causal link between higher IQ and an increased risk of PD.